Pelatihan Pencatatan dan Pelaporan Keuangan dengan Zahir Accounting Di Yayasan Raudhah Syarifah Kabupaten Purwakarta - Lukmanul Hakim; Dede Firmansyah Saefudin; Suhardi Suhardi; Ratnawati Ratnawati; Widi Witriani; Dita Meiliani (LPPM Universitas Bina Sarana Informatika, 2021)
The purpose of this community service activity (PkM) is to implement the management of financial reports with the desktop version of the Zahir Accounting application in educational institutions. Training is used as a method in PkM activities both offline and online with the Zoom Clouds Meeting application. The activity was held on Sunday 3 October 2021 at the Foundation Hall located in Purwakarta Regency. The conclusions from the results of the PkM implementation are: First, the financial recording and reporting training activities with Zahir Accounting as community service at the Raudhah Syarifah Foundation, Purwakarta Regency were successfully held. Second, Zahir Accounting Software can be implemented in educational institutions that are categorized as service companies. Third, the use of Zahir Accounting can improve the quality of financial recording and reporting. Fourth, there was an increase in the knowledge of participants by 81.8 percent and an increase in the skills of participants by 54.55 percent. Fifth, the level of participants' satisfaction with the implementation of PKM is in the high category. Recommendations for further activities are to increase the training time to two working days, increase case examples, and provide assistance when partner institutions implement the Zahir Accounting application.